Alkene metathesis - a tool for the synthesis of conjugated polymers - Bunz, Uwe H. F.; Mäker, Dominic; Porz, Michael (Macromolecular rapid communications, 2012)
Alkene metathesis is a superb methodology. We report the progress using alkene metathesis in the synthesis of polymeric organic semiconductors. Three classes of polymers have been synthesized using acyclic diene metathesis (ADMET) or ring opening metathesis polymerization (ROMP), viz., poly(acetylene)s (PA), poly(arylene-vinylene)s (PAV), and organometallic polymers. For PAs, ROMP of cyclooctatetraenes is best, whereas for PAV, both ADMET and indirect and direct ROMP are viable. Metathesis performs flawlessly with the correct monomers, as molybdenum and particularly the robust Ru carbenes demonstrate. When performing ROMP, one is often rewarded with structurally uniform polymers that can display very low polydispersities. Overall, metathesis is a powerful tool for the preparation of semiconducting polymers.